2019
DOI: 10.3390/v11030217
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest is a Conserved Function of Norovirus VPg Proteins

Abstract: Murine norovirus (MNV) viral protein genome-linked (VPg) manipulates the cell cycle to induce a G0/G1 arrest and gain a beneficial replication environment. All viruses of the norovirus genus encode a VPg protein; however, it is unknown if the G0/G1 arrest induced by MNV VPg is conserved in other members of the genus. RNA transcripts encoding a representative viral VPg from five norovirus genogroups were transfected into RAW-Blue murine macrophages, and the percentage of cells in each phase of the cell cycle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Then, the negative-sense genomic and subgenomic RNAs are used as templates for the synthesis of positive sense genomic and subgenomic RNAs [ 21 ]. These transcription reactions are catalysed by the RNA-dependent RNA-polymerase (RdRp, NS7), using de novo mechanisms for synthesis of negative-stranded RNA [ 99 , 100 ], and VPg-dependent mechanisms of positive sense genomic and subgenomic RNA synthesis in which the NS7 uses multifunctional VPg as a proteinaceous primer [ 23 , 25 , 101 ]. Multifunctional VPg [ 24 ] plays various roles in norovirus replication including induction of higher-order RdRp multimer or tubular fibril formation and enhancement of MNV RdRp activity [ 25 ].…”
Section: Replicative Cyclementioning
confidence: 99%
“…Then, the negative-sense genomic and subgenomic RNAs are used as templates for the synthesis of positive sense genomic and subgenomic RNAs [ 21 ]. These transcription reactions are catalysed by the RNA-dependent RNA-polymerase (RdRp, NS7), using de novo mechanisms for synthesis of negative-stranded RNA [ 99 , 100 ], and VPg-dependent mechanisms of positive sense genomic and subgenomic RNA synthesis in which the NS7 uses multifunctional VPg as a proteinaceous primer [ 23 , 25 , 101 ]. Multifunctional VPg [ 24 ] plays various roles in norovirus replication including induction of higher-order RdRp multimer or tubular fibril formation and enhancement of MNV RdRp activity [ 25 ].…”
Section: Replicative Cyclementioning
confidence: 99%
“…Furthermore, it was identified that the cell cycle arrest is induced by the conserved motif KGKxKxGRG in the N-terminal region which is found in the VPg proteins of all the norovirus genogroups, except for GIII. These findings demonstrate that the N-terminal end of VPg is essential to arrest the cell cycle in G1/G0 and promotes HuNoV replication (69). Therefore, the interactions of VPg with the RdRp and cellular components of the host play an important role in the viral replicative cycle and the pathogenesis of HuNoV.…”
Section: Vpgmentioning
confidence: 76%
“…The conserved N-terminal region of norovirus VPg proteins is involved in binding of NTPs, nucleotidylation, and cell cycle manipulation [ 11 , 17 , 25 ]. We were interested in determining if mutations that eliminate RNA binding have any effect on the cell cycle, as previously this has only been investigated in relation to single point mutations or truncations of the motif [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conserved N-terminal region of norovirus VPg proteins is involved in binding of NTPs, nucleotidylation, and cell cycle manipulation [ 11 , 17 , 25 ]. We were interested in determining if mutations that eliminate RNA binding have any effect on the cell cycle, as previously this has only been investigated in relation to single point mutations or truncations of the motif [ 17 ]. To determine the importance of positively charged amino acids for a G0/G1 cell cycle arrest, mRNA transcripts encoding MNV VPg TM and MNV VPg K2-12 were transfected into asynchronous RAW-Blue cells and the percentage of cells in each phase of the cell cycle measured by flow cytometry ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation